Analisis Tantangan dan Peluang Pemanfaatan Teknologi Digital dalam Mengembangkan Bisnis UMKM - Rizqina Tahta Auliya (Yayasan Al Ma'arif Dawuhan, 2025)
This article examines the challenges and opportunities faced by Micro, Small, and Medium Enterprises (MSMEs) in Semarang City in utilizing digital technology for business development. Digital technology, such as social media marketing and e-commerce, presents significant opportunities to expand market reach and enhance operational efficiency. However, challenges such as low digital literacy, limited financial resources, and inadequate infrastructure remain major obstacles. This study employs a literature review method to gain a deeper understanding of these issues. The findings indicate that digital literacy training, access to technology, and consistent policy support are crucial in empowering MSMEs in the digitalization era. By improving digital competence and providing financial and technological support, MSMEs can optimize digital tools to enhance competitiveness and business sustainability. Furthermore, government policies play a vital role in facilitating digital adoption through regulatory frameworks, incentives, and infrastructure development. Addressing these challenges requires collaboration between various stakeholders, including the government, financial institutions, and private sector actors, to create a conducive ecosystem for MSME growth. This study contributes to the existing literature by highlighting the key factors influencing digital adoption among MSMEs and providing insights for policymakers in formulating strategies to support digital transformation. Future research should explore empirical case studies to assess the effectiveness of digitalization programs and identify best practices for MSME development. These efforts are essential to ensuring that MSMEs can fully leverage digital technology, thereby fostering economic resilience and sustainable growth in the digital economy.